Emotional loneliness, perceived stress, and academic burnout of medical students after the COVID-19 pandemic - Malakcioglu, Cem (Frontiers in Psychology, 2024)
Emotional loneliness has been increasing among young people nowadays, despite their intense social interaction via virtual platforms and real life. Their social-emotional development seems to be interrupted due to high levels of psychological stress and it probably results in significant academic problems. It was aimed to investigate the relationships between loneliness, perceived stress, and academic burnout of medical students after COVID-19 pandemic.Methods: Data sets were collected from 630 medical students (51.7% females, the mean age is 21.31 and the SD is 2.14) by using scales for emotional and social loneliness, psychological stress, and academic burnout in January 2023. After verifying normality, t-test and ANOVA were used to compare groups. Pearson correlation and path analyses were also utilized for data analysis.Results: For loneliness, there are significant differences between gender, and preclinical and clinical terms groups while stress levels are significantly different between terms. Males are much lonelier emotionally and totally than females. No significant difference is observed for academic burnout across gender and term groups. Perceived stress plays a mediator role between emotional loneliness and academic burnout while social loneliness has almost no effect on both stress and academic burnout. Stress increases significantly as educational levels increase.According to the results, eEmotional loneliness and stress increase academic burnout. To alleviate the burnout, emotional loneliness and stress should be decreased by various psychosocial interventions, such as group therapies, to address these issues and improve the psychological resilience of medical students.for students.